Liquid Assimilation in Havana Spanish - Hwu, Fenfang (Kansas Working Papers in Linguistics, 1991)
There has been a consensus that Laryngeal and Supralaryngeal nodes are located under the Root node and Place node is under the Supralaryngeal node (Clements 1985, Sagey 1987, Archangels and Pulleyblank 1986). There is, however, very little consensus on where manner of articulation features belong. It will be argued in this paper, basing on spreading and delinking process occurring in Liquid assimilation in Havana Spanish, that 1) the [continuant] feature should be located under the Supralaryngeal node 2) [continuant] and place features form a natural class node: Oral Cavity as proposed in Clements (1987) 3) manner features and place features do operate together in the delinking and spreading operations.